A new troglobitic genus of the family Theridiidae Sundevall, 1833 (Araneae: Theridiidae) from China - Hu, Changhao; Liu, Jie (Zootaxa, 2025)
A new genus of the subfamily Theridiinae Sundevall, 1833, Troglotheridion gen. nov., with the type species Troglotheridion lamellatum sp. nov. (male, female) and an additional species: Troglotheridion sangzhiense (Zhu, 1998) comb. nov. (male, female) ex. Theridion Walckenaer, 1805 is described. Both species of the new genus are restricted to caves in Yunnan-Guizhou Plateau, China, and have much vestigial eyes and lost pigment. Diagnoses, descriptions, photos of both species and a distribution map are provided.